The Religiosity of Javanese Society in Modern Indonesian Literature - Wulandari, Patricia (HM Publisher, 2021)
A good literary work can provide information about various kinds of community life, including life-related to religiosity. Literary works are closely related to religiosity, and because of that, various works appear showing the religiosity of society, one of which is the Javanese. Modern Indonesian literary works that illustrate this are the collection of short stories from Umi Kalsum by Djamil Suherman, the lyrical prose Pengakuan Pariyem by Linus Suryadi AG, and the novel Ronggeng Dukuh Paruk by Ahmad Tohari. Each of these works represents the diversity of Javanese society. The collection of short stories from Umi Kalsum shows the religious side of the community called the santri, who are so obedient in carrying out their worship. The lyrical prose of Pariyem's confession provides information on how a babu is so resigned to seeing life, but in her soul holds the wisdom of Kejawen. Meanwhile, Ronggeng Dukuh Paruk describes the Javanese people who worship the spirits of their ancestors. Even though they have different religions, they basically want harmony. Javanese people who live in santri enjoy harmony when they live with strong Islamic values. The Javanese people of the Gunung Kidul area live in harmony if they are always accept and see life as it is according to its Javanese nature. The Dukuh Paruk community attains harmony that originates from the worship of the spirit of Ki Secamenggala